2021
DOI: 10.1097/pcc.0000000000002780
|View full text |Cite
|
Sign up to set email alerts
|

Driving Pressure and Normalized Energy Transmission Calculations in Mechanically Ventilated Children Without Lung Disease and Pediatric Acute Respiratory Distress Syndrome*

Abstract: To compare the new tools to evaluate the energy dissipated to the lung parenchyma in mechanically ventilated children with and without lung injury. We compared their discrimination capability between both groups when indexed by ideal body weight and driving pressure. DESIGN:Post hoc analysis of individual patient data from two previously published studies describing pulmonary mechanics. SETTING:Two academic hospitals in Latin-America. PATIENTS:Mechanically ventilated patients younger than 15 years old were inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
20
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 34 publications
2
20
0
1
Order By: Relevance
“…Although Diaz stated in their study that the ΔP value better discriminates ARDS than all formulas including MP, Rauf et al stated in their study that the driving pressure value in pediatric patients was most effective factor for MV-related days and pediatric intensive care unit (PICU) length of stay, but not for mortality (13,25). In our patients, the driving pressures were below 15 cmH 2 O in both Group V and Group P. However, there are multiple risk factors for VILI, and considering driving pressures alone would only be looking at risks from one angle.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…Although Diaz stated in their study that the ΔP value better discriminates ARDS than all formulas including MP, Rauf et al stated in their study that the driving pressure value in pediatric patients was most effective factor for MV-related days and pediatric intensive care unit (PICU) length of stay, but not for mortality (13,25). In our patients, the driving pressures were below 15 cmH 2 O in both Group V and Group P. However, there are multiple risk factors for VILI, and considering driving pressures alone would only be looking at risks from one angle.…”
Section: Discussionmentioning
confidence: 96%
“…A portion of the applied energy is reflected in the tissues as excessive stretching, volume or pressure damage, and heat. Both resistance and elastance of pediatric patients are different from adults (13). In these patients, airway resistance is high, After the MP calculation formula applied by Gattinoni et al for VCV, Becher et al showed the MP calculation formula for PCV.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Presented data is the worst during the first 72h of admission, so time-dependent variables are not analyzed 43 . We did not investigate other parameters associated with PARDS severity or outcomes, i.e., dead space or mechanical power, because it was not part of our objective [53][54][55] . As in many multicenter studies, there might be differences in ventilatory strategy between sites, and comparisons were not possible given the heterogeneity of cases per center.…”
Section: Discussionmentioning
confidence: 99%
“…The formal recognition of pediatric critical care medicine led to improvement not only in those being trained but also in those doing the training. It elevated the bar for the entire specialty by elevating the bar of expectations of training pathways, which extends to maintenance of certification, self-assessment, and the ongoing improvement of care (5,6).…”
mentioning
confidence: 99%